The safety of percutaneous renal biopsy for acute kidney injury in metastatic renal cell cancer patients with reduced nephron mass - Milanez, Tomaz; Srinivasan, Vinay; Premru, Vladimir; Arnol, Miha; Ocvirk, Janja; Jaimes, Edgar A. (Frontiers in Nephrology, 2025)
BackgroundPercutaneous renal biopsy (PRB) provides valuable information to guide treatment decisions in patients with metastatic renal cell carcinoma (mRCC) who develop acute kidney injury (AKI) after systemic anticancer therapy (SACT). The rising incidence of renal cell carcinoma (RCC) and the substantial impact of SACT on overall survival suggest a higher prevalence of RCC patients with reduced nephron mass and a solitary kidney (SK) requiring PRB for AKI. However, safety data on SK biopsies are scarce, and the potential for dialysis-requiring complications may deter clinicians.MethodsThis retrospective case series reports the safety of 13 PRBs in 12 mRCC patients with reduced nephron mass who developed AKI during SACT as well as six PRBs in six patients with metastatic solid malignancies and AKI, which developed during SACT.ResultsEleven biopsies in mRCC patients and five biopsies in patients with metastatic solid malignancies were uneventful. One patient with mRCC experienced a major bleeding event due to an arteriovenous (AV) fistula seven days post-procedure, while another mRCC patient developed macrohematuria within 24 hours. In the group of patients with metastatic solid malignancies, one patient experienced a small perinephric hematoma during the observational period. Despite the small sample size, individual chart reviews and direct management of adverse events allowed assessment of the association between biopsy and complications.ConclusionUntil further data become available, a longer observation period is recommended for these patient cohorts compared to the general population. Further studies are needed to develop consensus guidelines for PRB in mRCC patients with reduced nephron mass.